2014
DOI: 10.1039/c3dt53134a
|View full text |Cite
|
Sign up to set email alerts
|

Stable core-modified calixsmaragdyrins: synthesis, structure and specific sensing of the hydrogen sulfate ion

Abstract: Stable calixoxa- and calixthiasmaragdyrins containing three methine bridges and two direct bonds connecting the five pyrrole/heterocycle rings were synthesized by [3 + 2] condensation of dipyrromethane with 16-oxatripyrrane and 16-thiatripyrrane respectively under mild acid-catalyzed conditions. The compounds were characterized by HR-MS, 1D & 2D NMR, absorption and electrochemical techniques and the structure of calixoxasmaragdyrin was solved by X-ray crystallography. The crystal structure analysis indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…As anion binding properties of RTXN1 has already been established by 1 H‐NMR studies, at this juncture, we are curious to explore the effect of anion binding on the irreversible redox waves of the rotaxane. Although, most of the host systems utilized in the anion binding studies are of reversible in nature, ] anion binding using irreversible redox wave‐based system is rarely reported …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…As anion binding properties of RTXN1 has already been established by 1 H‐NMR studies, at this juncture, we are curious to explore the effect of anion binding on the irreversible redox waves of the rotaxane. Although, most of the host systems utilized in the anion binding studies are of reversible in nature, ] anion binding using irreversible redox wave‐based system is rarely reported …”
Section: Resultsmentioning
confidence: 96%
“…Although, most of the host systems utilized in the anion binding studies are of reversible in nature, [13] ] anion binding using irreversible redox wave-based system is rarely reported. [18] In this regard, the electrochemical titration of RTXN1 is carried out with all of the TBAanions (OAc À , HSO 4 À , Cl À , H 2 PO 4 À and NO 3 À ) ( Figure 8. and Figure 40S-42S, ESI †) in DMF solvent at 298 K. In each case, aliquots of TBAanion solution in anhydrous DMF is added gradually to the electrochemical solution of RTXN1 (1 mM) upto 10 equiv.…”
Section: Anion Binding Property Of Rtxn1 By 1 H-nmr Titration and Elementioning
confidence: 99%
See 1 more Smart Citation
“…Calixsmaragdyrins are a rare class of molecules, in that Ravikanth et al. reported aza‐, oxa‐, and thia‐calixsmaragdyrins 8 only by the acid‐catalyzed condensation reactions [5a,b] . They also demonstrated that oxa‐calixsmaragdyrin served as an effective ligand toward Pd II and Ru II metals [6] .…”
Section: Methodsmentioning
confidence: 99%
“…However, the preparation of stable azasmaragdyrin has remained elusive, and this has prevented its potential application as a ligand to form metal complexes. Recently, we reported the first successful synthesis of stable meso -aryl calixsmaragdyrin 2 , where introduction of one sp 3 meso -carbon atom instead of a sp 2 meso -carbon atom provides increased flexibility and stability to the smaragdyrin core. The calixsmaragdyrin macrocycle 2 has three ionizable inner NH atoms which indicate its potential for multidentate coordination chemistry. Given the limited stability of smaragdyrin 1 it is not currently possible to explore its role as a potential ligand in coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%